Manajemen Pajak Terhadap Penghasilan Pajak Badan Berdasarkan UU Pajak Penghasilan di PT Melakim Inti Perkasa - Stefvy Stefvy; Denny Salim; Diana Afriani (Politeknik Ganesha Medan, 2025)
Self-assessment system can cause the possibility of overpayment or underpayment as well as the wrong report of taxes, therefore, tax review is required in order to check whether the tax obligations are already in compliance with the Tax Provisions to avoid tax penalties. This research is done in PT Melakim Inti Perkasa which is engaged in selling laboratory equipment & chemical and providing service repair the laboratory equipment. The purpose of this research is to know the implementation of Entity Income Tax obligation through tax review. Types of this research is descriptive research with case study in PT Melakim Inti Perkasa and the research object is tax review of entity’s income tax in PT Melakim Inti Perkasa for year 2023. Data which is collected is secondary data. Research result shows that based on the results of the analysis and evaluation conducted by the writer on the fiscal reconciliation is the company does not conduct fiscal reconciliation properly. The company does not conduct fiscal correction for some revenue and expenses in the amount Rp.99,841,990.00 which can increase the taxable income after tax review. Therefore, the company should pay additional income tax in amount Rp.17,392,943.00 to tax office with the fines in amount Rp.3,805,144.00.